Influence of inter-dendritic segregation on the precipitation behaviour and mechanical properties in a vanadium-containing Fe–Cr–Ni–Mo weld metal. (September 2020) - Sun, Jian; Lu, Shanping
Abstract: A novel Fe–Cr–Ni–Mo weld metal containing different V content was designed and fabricated by gas metal arc welding and post-weld heat treatment. The excellent mechanical properties with a combination of high strength and good toughness were obtained by synergistic effect of nanoscale carbides, high-density dislocations and small subgrains. The discrete nanoscale carbides were characterised by transmission electron microscopy and atom probe tomography. Moreover, it was firstly found that the precipitation sites of nanoscale carbides were mainly located at inter-dendritic regions instead of dendritic core regions owing to the heterogeneous distribution of alloying elements. Graphical abstract: Image, graphical abstract